Creative Leadership of School Administrators under the Chachoengsao Secondary Educational Service Area Office - โกสิยารักษ์, ศศิกาญจน์; แก้วมงคล, ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: (1) examine the creative leadership of school administrators; (2) compare the creative leadership of school administrators; and (3) investigate guidelines for promoting the creative leadership of school administrators. The sample consisted of 281 teachers from schools under the Chachoengsao Secondary Educational Service Area Office. The sample size was determined using the Krejcie and Morgan table (1970), and the participants were selected through stratified random sampling, with schools as the sampling units, followed by simple random sampling using the lottery method. The research instruments included a five-point rating scale questionnaire. This questionnaire demonstrated strong content validity, with the Index of Item-Objective Congruence (IOC) ranging between 0.80 and 1.00. The reliability of the instrument was also high, yielding a coefficient of 0.833 and a semi-structured interview form. Data were analyzed using a statistical software package. The statistical methods employed were frequency, percentage, mean, standard deviation, t-test, and F-test.          The research findings revealed that: 1. The overall level of creative leadership of school administrators under the Chachoengsao Secondary Educational Service Area Office was rated at a high level. (x̄= 4.21, S.D. = 0.145) When considered by dimension, flexibility received the highest mean score (x̄= 4.24, S.D. = 0.210, followed by imagination (x̄= 4.23, S.D. = 0.200), while trust obtained the lowest mean score (x̄= 4.16, S.D. = 0.195); however, all dimensions were still evaluated at a high level. 2. Teachers with different genders demonstrated significantly different perceptions of administrators’ creative leadership at the .01 level. In contrast, no significant differences were found in overall perceptions based on teachers’ educational level or school size. 3. The guidelines for developing the creative leadership of school administrators under the Chachoengsao Secondary Educational Service Area Office consisted of four dimensions, with four corresponding development approaches